On the Front Line: The Role of Physical Educators in Preventing Student Suicide. Issue 3 (25th April 2022) - Whisenhunt, Julie; Biber, Duke; Heidorn, Brent
Abstract: This article provides general information and guidance for physical educators, specifically related to their role in suicide prevention. It is the duty of school personnel to recognize the vital role they have in helping to prevent suicide, to promote healthy behaviors and positive relationships, and to appropriately talk about suicide and suicide attempts. Physical educators, therefore, should have knowledge of the risk factors, understand the underlying concepts of suicidal behaviors, be aware of their responsibility to help educate others, and provide meaningful teacher- and student-based modeling and mentoring opportunities in physical education programs.